2005
DOI: 10.1136/bmj.331.7531.1517
|View full text |Cite
|
Sign up to set email alerts
|

Depictions of substance use in reality television: a content analysis of The Osbournes

Abstract: 19 Ylikahri RH, Leino T, Huttunen MO, Poso AR, Eriksson CJ, Nikkila.Effects of fructose and glucose on ethanol-induced metabolic changes and on the intensity of alcohol intoxication and hangover. Review methods Three reviewers watched all 10 episodes of the first season and coded incidents of substance use according to the substance used (alcohol, tobacco, or drugs), the way use was portrayed (visually or verbally), the source of the message (the character in the show involved in the incident), and the slant o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 6 publications
1
32
0
Order By: Relevance
“…In fact, a study of the reality program The Osbournes showed that the same character who was at times endorsing alcohol was also depicted as rejecting alcohol (Blair et al, 2005). A similar pattern was found in a study focused on the teen television series The O.C., where the messages about alcohol alternated between depicting positive and negative outcomes, both often within the same episode (Russell, 2006).…”
Section: Alcohol Messages In Television Seriesmentioning
confidence: 60%
See 2 more Smart Citations
“…In fact, a study of the reality program The Osbournes showed that the same character who was at times endorsing alcohol was also depicted as rejecting alcohol (Blair et al, 2005). A similar pattern was found in a study focused on the teen television series The O.C., where the messages about alcohol alternated between depicting positive and negative outcomes, both often within the same episode (Russell, 2006).…”
Section: Alcohol Messages In Television Seriesmentioning
confidence: 60%
“…One key finding is that the messages contained in the television programs are often mixed. Positive messages about drinking include its association with humor, valued outcomes such as camaraderie and fun social times (Hundley, 1995), or other forms of positive endorsements (Blair et al, 2005). These positive messages are often fueled by the practice of product placement, and, in fact, alcohol is one of the most actively placed product categories in television programs and movies in Hollywood (Russell and Belch, 2005); for example, in 1998, alcohol placements occurred in 181 television series at least once during the season (Evans and Kelly, 1999).…”
Section: Alcohol Messages In Television Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…We were, therefore, interested in examining the nature and content of this online alcohol social marketing campaign embedded in a popular TV soap, whose characters would be familiar to young viewers and might potentially have influence upon health behaviours and beliefs. Similar analyses have presented depictions of substances in the popular television shows The Osbournes and The OC, concluding that there were often contradictory messages presented about use (Blair, Yue, Singh, & Bernhardt, 2005;Bulke, Simons & Van Gorp, 2009). However, these types of TV programmes are intended solely for entertainment and not as health interventions.…”
Section: The Know Your Limits Campaignmentioning
confidence: 85%
“…The amount of TV viewing in youth is also linked with smoking (Gidwani et al 2002;Gutschoven & van den Bulck 2004;Gutschoven & van den Bulck 2005;Hancox, Milne & Poulton 2004). One detailed content analysis of MTV's reality show The Osbournes indicated that TV could deliver numerous messages related to the use of alcohol, tobacco, and other drugs, with more depictions implying endorsement than rejection of use (Blair et al 2005). There has been some systematic analysis of tobacco imagery on television including the US suggesting about one "smoking act" per hour of programming (Christenson, Henriksen & Roberts 2000) and about 2.5 % of TV prime time characters smoking (Long et al 2002), while Japanese research indicates four smoking acts per hour and virtually no negative portrayals of smoking (Kanda et al 2006;Sone 1999), and about two scenes in New Zealand's TV containing such imagery for every hour of programming (McGee & Ketchel 2006).…”
mentioning
confidence: 99%